The Role of Developmental Assets in Gender Differences in Anxiety in Spanish Youth - Gomez-Baya, Diego; Salinas-Perez, Jose A.; Sanchez-Lopez, Alvaro; Paino-Quesada, Susana; Mendoza-Berjano, Ramon (Frontiers in Psychiatry, 2022)
Anxiety disorders are the most prevalent psychological disorders during emerging adulthood. Some consistent gender differences have been reported in anxiety, with women suffering more anxiety than men, what has detrimental consequences in most life spheres in youth and later life stages. The understanding of the development of anxiety in emerging adulthood requires a developmental perspective. Developmental Assets Theory was postulated to describe the individual and the contextual resources which may foster positive youth development and mental health. The present work aims to analyse to what extent the gender differences in anxiety may be partly explained by gender differences in developmental assets. For this purpose, a cross-sectional study was conducted, in which a sample of 1044 youth (75.5% women; Age range = 18 - 28; M age = 20.47, SD = 3.08) enrolled in 11 universities from different regions in Spain filled in self-report measures of developmental assets and anxiety symptoms. Participants completed an online survey with the scales Developmental Assets Profile, developed by the Search Institute (Scales, 2011), and Generalized Anxiety Disorder-7 (GAD-7; Spitzer et al., 2006). Results showed more anxiety in female subsample (at both symptoms and clinical levels), and some gender differences in developmental assets were also observed. A partial mediation model, based on regression analyses, indicated that gender differences in anxiety were partly explained by gender differences in confidence and caring. Thus, higher anxiety in women was partly due to lower scores in positive identity and higher scores in positive values. These results suggested the need to design programs to prevent anxiety with specific measures for women youth, in order to nurture positive identity and to promote strengths and coping skills that allow them to reach the benefits for wellbeing derived from positive values, thus preventing worry and stress overload, which may lead to anxiety.